Generation-dependent non-educational characteristics of medical students - Azarmidokht Firoozjahantighi; Fariba Jowkar; Fariba Haghani (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Educational centers accommodate people of varying generations. Indeed, each generation has its specific priorities and values that affect its performance and decisions in various aspects, including educational aspects. Understanding the traits of members of a given generation facilitates understanding how their performance can be improved inside and outside the classroom. So, this study was designed to identify the non-educational characteristics of MD students in the universities of medical sciences in Iran. MATERIALS AND METHODS: The present study adopted a qualitative exploratory approach. Data were collected through face-to-face, semi-structured interviews. Participants included general medicine students who had completed at least one semester. Sampling was purposive with maximum variation. Sampling was continued until data saturation, and a total of 32 interviews were conducted. Graneheim and Lundman's content analysis approach was adopted to analyze the data. Lincoln and Guba's reliability criteria were used to achieve the accuracy and reliability of the data. RESULTS: A total of 32 students were interviewed (n = 18 women and n = 14 men; age range: 19-27 years). The participants had completed 2-13 semesters and had between one and six siblings. A total of 10 major categories emerged as the generational traits of students. The main categories included devoted parents, money as the key reference of value, non-sexism, religious perplexity, experiencing oneself with others, my life's address, tunnel vision, evasion from responsibility, winning fame, and I and nothing else. CONCLUSION: For them, gender and religion have lost their former meaning and they believe in more freedom. They are also one-dimensional people, lethargic and night people, who evade responsibility and have a strong desire to be seen, approved, and respected. They also prioritize themselves and their peace of mind. Since these characteristics can have many direct and indirect effects on various aspects of their lives, including the educational aspect, it can be very beneficial for people interacting with them to identify and consider these characteristics.